Resposta do capim-tanzânia à aplicação de manganês - Sylvestre, Thiago de Barros [UNESP]; Kuhnen, Fernando [UNESP]; da Silva, Elcides Rodrigues [UNESP]; Silva Martins, Paulo Eduardo [UNESP]; Galatti, Francine de Souza [UNESP]; Prado, Renato de Mello (Universidade Federal de Uberlândia (UFU), 2012)
The objective was to evaluate the influence of the manganese nutritional status, growth and dry matter production of Tanzania grass. For this, we used plants of Panicum maximum Jacq. cv. Tanzania grown in pots filled with Oxisol (Mn = 0.6 mg dm(-3)). The experimental design was completely randomized, with five doses of manganese (0, 15, 30, 60 and 120 mg dm(-3)) and four replications. The plant shoot were harvested twice, the first 42 days after sowing and the second, 30 days after the first cut. In the two sections were evaluated the number of tillers and leaves, steam diameter, plant height, shoot dry matter and in shoot-Mn concentration and root dry matter after the second cut. The application of manganese in the soil increased the levels of this nutrient in the soil and their uptake by grass, which was more than four times fold higher in the second cut compared to the first cut. The use of high rates of Mn did not affect the growth of Panicum maximum, and decreased dry matter production only for the sum of two cuts, indicating high tolerance of forage of Mn toxicity. The toxicity of Mn in forage was associated with leaf content in the first and second cut of 1,238 and 1,418 mg kg(-1), respectively.

Objetivou-se avaliar a influência da aplicação de manganês no estado nutricional, no crescimento e na produção de matéria seca do capim-tanzânia. Para isto, utilizou-se plantas de Panicum maximum Jacq. cv. Tanzânia cultivadas em vasos preenchidos com amostras de um Latossolo Vermelho distrófico (Mn=0,6 mg dm-3). O delineamento experimental utilizado foi inteiramente casualizado, constituído de doses de manganês (0, 15, 30, 60 e 120 mg dm-3) e quatro repetições. Foram realizados dois cortes, o primeiro após 42 dias da semeadura e, o segundo, 30 dias após o primeiro corte. Nos dois cortes foram avaliados número de folhas e perfilhos, diâmetro do colo, altura das plantas, matéria seca de parte aérea e teor de Mn na parte aérea e a matéria seca de raízes após o segundo corte. A aplicação do manganês no solo incrementou os teores desse micronutriente no solo e sua absorção pela forrageira, que foi mais de quatro vezes maior no segundo corte comparado ao primeiro corte. O emprego de altas doses de Mn não afetou o crescimento do capim-tanzânia, e diminuiu a produção de matéria seca apenas para soma dos dois cortes, indicando alta tolerância da forrageira a toxicidade de Mn. A toxicidade de Mn na forrageira esteve associada com teor foliar no primeiro e no segundo corte de 1.238 e 1.418 mg kg-1, respectivamente.
Response Tanzania grass to application of manganese
Keywords: Panicum maximum; Grass; Fertilization; Micronutrient